2007
DOI: 10.1590/s1519-69842007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying management units in non-endangered species: the example of the sloth Bradypus variegatus Schinz, 1825

Abstract: In this study we propose the analysis of genetic diversity of the common three-toed sloth, Bradypus variegatus, in an attempt to understand population structure, identify divergent intraspecific units, and contribute to the knowledge of biodiversity in the neotropical forests. We analyzed a 387 bp segment of the mitochondrial DNA control region in 28 individuals distributed in different localities of both Atlantic and Amazon forests. Our results demonstrated that the genetic diversity of B. variegatus is distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, we chose to describe two vertebrate components within the Northerly BAF, not only because of the panbiogeographical convergence zone, but also because this regions is shown to be one of the most important connection bridges between the Atlantic and the Amazonian forests for mammals (Costa, 2003; Moraes‐Barros, Miyaki & Morgante, 2007; Tchaicka et al ., 2007) and for birds (Ribas & Miyaki, 2004; Cabanne et al ., 2008; Vilaça & Santos, 2010) and for the colonization of the eastern Atlantic coast by amphibians (Carnaval & Bates, 2007). Also, there is evidence that the northern Atlantic coast was the most probable route linking those forests (De Oliveira, Barreto & Suguio, 1999; Silva & Bates, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we chose to describe two vertebrate components within the Northerly BAF, not only because of the panbiogeographical convergence zone, but also because this regions is shown to be one of the most important connection bridges between the Atlantic and the Amazonian forests for mammals (Costa, 2003; Moraes‐Barros, Miyaki & Morgante, 2007; Tchaicka et al ., 2007) and for birds (Ribas & Miyaki, 2004; Cabanne et al ., 2008; Vilaça & Santos, 2010) and for the colonization of the eastern Atlantic coast by amphibians (Carnaval & Bates, 2007). Also, there is evidence that the northern Atlantic coast was the most probable route linking those forests (De Oliveira, Barreto & Suguio, 1999; Silva & Bates, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The most widespread of the 3-toed sloths, the brownthroated sloth B. variegatus presented 2n = 54, but 4 males with 2n = 55 were described, and the extra chromosome was interpreted as an additional Y [Jorge et al, 1985a;Goldschmidt and Almeida, 1993;Goldschmidt et al, 1995]. Although this species has several subspecies and separate populations have been identified [Moraes- Barros et al, 2007;Gardner, 2008], no detectable chromosome differences, besides the extra Y chromosome, were reported.…”
Section: Slothsmentioning
confidence: 99%
“…Taxonomic Note: Seven subspecies are recognized according to Gardner (2007). Recent phylogeographic studies revealed that B. variegatus from the Central American, western Amazon and Atlantic forests constitute distinct and unique evolutionary units that are distinguishable by molecular and morphological traits (Moraes- Barros et al, 2002Barros et al, , 2006Barros et al, , 2007.…”
Section: Bradypus Tridactylus Least Concern (Lc)mentioning
confidence: 99%